Theoretical Study on Structures of Graphite-Like Boron-Nitride Clusters - Feng, Yan; Fang, Fang (Asian Journal of Chemistry, 2012)
A novel set of graphite-like structures of BmNn (m + n £ 54, m = n or m = n + 1) clusters are obtained. The size of those particularly stable clusters increases with the regular interval of 3, 3 and 2. The structures of those particularly stable clusters mainly adopt two stacking modes of hexagons. This packing motif and the increasing interval are helpful to understand and predict the stable structures of the larger size of graphite-like boron-nitride clusters.